Scenario Indonesia Tahun 2025 dan Tantangan yang Dihadapi oleh Administrasi Publik - Salomo, Roy V. (UI Scholars Hub, 2011)
The research aimed to construct the scenario of sub-national government administration in Indonesia and its available alternatives. The approach used was qualitative approach with the method of focus group discussion (FGD) and in-depth interview with economic and social politicians and bureaucrats. In addition secondary data were used to support the result. Two scenarios of the environment of Indonesian sub-national administration for 2025 are gained from two FGDs: the Utopian Scenario and Tumble into the Gutter Scenario. According to the first FGD, the utopian scenario is less likely to happen within the next 20 years, while the tumble-into-the-gutter scenario is considered more likely, especially if the recent condition is long-drawn-out, the homework is never done, and there is lack of awareness from national and local political elites on the recent crisis.